Weight optimization of steel frames with cellular beams through improved hunting search algorithm. Issue 5 (April 2020) - Dogan, Erkan; Ozyuksel Ciftcioglu, Aybike
Hunting search method–based optimum design algorithm is presented to investigate the weight optimization of steel frames with cellular beams. Unlike practical applications where rolled sections are assigned to both the beams and columns, built-up sections are used for beams. Design specifications including the design of steel frames and that of cellular beams are taken from Load and Resistance Factor Design–American Institute of Steel Construction. The algorithm presented selects optimal W-sections to be used for the members of the unbraced plane frame from the ready section pool of the same code. In addition, number of holes and hole diameter of the beams are selected for optimal frame by the algorithm for satisfying the design constraints and making the weight of the frame to be minimum. Besides, Levy Flight procedure is also adopted to the simple hunting search method for better designs. Optimized steel frames with cellular beams are then analyzed by ABAQUS three-dimensional finite element software. The results attained from nonlinear finite element analysis of the steel frames are then taken into account for comparison with optimization outcomes. Results reveal that designing the beam members as cellular beams reduces the weight of the frame.